PENGARUH KUALITAS PRODUK DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN PADA PADMA HERBAL BALI DI KABUPATEN TABANAN - NI GUSTI AYU PUTRI NURYATI; I NYOMAN GEDE MARTA; I GUSTI AYU META PURMINA DEWI (Universitas Mahendradatta, 2023)
With the advancement of technology in various fields like today,the business world is increasingly competitive in business, especially inIndonesia which is marked by the existence of herbal companies that offermany quality herbal products and are able to compete in the market. Everycompany always tries to maintain the company's survival by makingeffective and quality products so that customers feel satisfied and remainloyal to the company. Padma Herbal is a herbal company that marketshealth products, because the quality of its products has been highly trustedby consumers from year to year, making this company grow rapidly.Seeing this background, this thesis is entitled: